2006
DOI: 10.1007/s00367-006-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

The French Atlantic margin and deep-sea submarine systems

Abstract: The sedimentary infill of the Bay of Biscay off Ireland, UK, France and Spain took place in four phases. The last one (35 Ma to present) is characterised by gravitational, pelagic, contouritic and glacigenic processes leading to the setup of three deep sea systems. To the North, the Celtic and Armorican fans are fed by a "canyon-dominated" margin and its connection with the "Manche" palaeoriver, which drained a large area of western Europe. To the South, the Cap-Ferret fan results from the evolution of a "tect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Details about cores and coring sites are given in Figure 1 and Table 1. These sites are situated far from any turbiditic influences which make them suited for recording continuous sediment input variability from the 'Fleuve Manche' palaeoriver throughout the last few glacial periods (Bourillet et al, 2003;Bourillet et al, 2006). Physical properties of the cores were determined onboard by measuring the P-wave velocity and gamma-ray attenuation density every 2 cm using a 'Geotek Multi Sensor Core Logger' (MSCL).…”
Section: Core Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details about cores and coring sites are given in Figure 1 and Table 1. These sites are situated far from any turbiditic influences which make them suited for recording continuous sediment input variability from the 'Fleuve Manche' palaeoriver throughout the last few glacial periods (Bourillet et al, 2003;Bourillet et al, 2006). Physical properties of the cores were determined onboard by measuring the P-wave velocity and gamma-ray attenuation density every 2 cm using a 'Geotek Multi Sensor Core Logger' (MSCL).…”
Section: Core Materials and Methodsmentioning
confidence: 99%
“…In contrast, deep-sea sediments, because of their continuous record of Earth's climate variability, offer an invaluable alternative to the usually discontinuous continental sequences to reconstruct the freshwater and sediment discharges of lowstand rivers and to detect the imprint of surrounding ice sheet oscillations and attendant modification of hinterland drainage directions. The deep-sea sedimentation in the northern Bay of Biscay (Armorican margin -NE Atlantic) has been strongly influenced by the 'Fleuve Manche' palaeoriver discharges throughout the glacial intervals of the Middle and Late Pleistocene (Bourillet et al, 2003;Mojtahid et al, 2005;Bourillet et al, 2006;Zaragosi et al, 2006;Eynaud et al, 2007;Toucanne et al, 2008). For the last deglaciation, Toucanne et al (2008) have recently shown downstream from the English Channel huge and extensive sediment accumulation with rates reaching up to 10 m ka -1 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a passive margin containing three parts; the Celtic, Armorican and Aquitaine margins (Zaragosi et al, 2000). Within this study, the Bay of Biscay was defined using geological boundaries (see Bourillet et al, 2006) therefore including all three margins, as the Celtic margin is part of the Celtic Sea according to hydrographical terms.…”
Section: Margin Morphologymentioning
confidence: 99%
“…Eight drainage basins occur from the Goban Spur to the Capbreton Canyon (Bourillet et al, 2006). Scleractinians were first reported in the Bay of Biscay in the late nineteenth century (e.g., Roule, 1896).…”
Section: Introductionmentioning
confidence: 99%
“…The duration of the current isolation of these sub-archipelagos embraces different climatic changes. On the one hand, the beginning of the Late Pliocene coincides with the change from a Subtropical climate [or warm-temperate (e.g., Fauquette et al, 1999)] to a Mediterranean one (e.g., Shackleton et al, 1984;Suc, 1984;Leroy and Dupont, 1994;Burkle, 1995;Bourillet et al, 2006). On the other hand, during the last 2.5 million years the Mediterranean area has been widely influenced by glaciations.…”
Section: Introductionmentioning
confidence: 99%